Taking the Lord's Name in Vain: The Impact of Connected Directors on 19th Century British Banks - Richard S. Grossman; Masami Imai (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper utilizes data on the presence of prominent individuals that is, those with political (e.g., Members of Parliament) and aristocratic titles (e.g., lords)–on the boards of directors of English and Welsh banks from 1879-1909 to investigate whether the appointment of well-connected directors enhanced equity value for bank shareholders. Our analysis of panel data shows that the appointment of connected directors did not increase the rate of return on bank equity. In fact, we find that the appointment of MPs to directorships had negative effects on bank equity returns. Our event-study analysis corroborates this finding, showing that a bank's shares exhibited negative abnormal returns when their directors were elected to Parliament. Taken together, our results indicate that connected directors yielded little–or even negative– economic payoff to bank shareholders in pre-war Britain.
Keywords: N23; 330; private finance; corporate governance; capital markets; banks; economic history